2020
DOI: 10.1039/c9sc05944j
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry dictates stability and oxidation state of supported single metal catalyst atoms

Abstract: Multi-response maps show that atomically dispersed iron on alumina provides relatively high activity and good stability in low temperature CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…This figure predicts the minimum required binding energies of single atoms (examples given for Pt, Pd, and Ni) on a support to obtain stable SACs for a day at the two indicated temperatures. In this study, we focused on idealized surfaces without defects (except for steps), hydroxyl groups or dopants, which may act as nucleation sites for sintering and in this way alter diffusion processes of metal adatoms [35][36][37] . Despite this simplification, the framework introduced is general and the correlations provide a guiding tool for initial materials selection.…”
Section: Stability Assessmentmentioning
confidence: 99%
“…This figure predicts the minimum required binding energies of single atoms (examples given for Pt, Pd, and Ni) on a support to obtain stable SACs for a day at the two indicated temperatures. In this study, we focused on idealized surfaces without defects (except for steps), hydroxyl groups or dopants, which may act as nucleation sites for sintering and in this way alter diffusion processes of metal adatoms [35][36][37] . Despite this simplification, the framework introduced is general and the correlations provide a guiding tool for initial materials selection.…”
Section: Stability Assessmentmentioning
confidence: 99%
“…Finally, we consider the kinetics of SA agglomeration which is a complex surface diffusion process with several time scales. 64 The traditional picture of SA agglomeration is based on either Ostwald ripening or coalescence. In both processes the decrease in the surface energy provides the driving force.…”
Section: Agglomeration Kineticsmentioning
confidence: 99%
“…Due to the distinct electronic structure and coordination environment of the isolated metal atoms supported on the support compared with metal clusters and nanoparticles, single-atom catalysts have shown exceptional catalytic performance in diverse applications. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] A survey of the single-atom catalysis research showed that around two-thirds of published articles in 2019 focused on liquid-phase reactions. Indeed, organic transformations widely used to synthesize fine chemicals are commonly conducted in solvents.…”
Section: Introductionmentioning
confidence: 99%